(untitled) (Bangladesh Journal of Medical Physics, 2014)
ECG is very important for diagnosis of cardiac disorders but most ECG equipment come from developed countries with very costly procurement and maintenance. Therefore, unless the technology is developed indigenously, common people in countries like Bangladesh will not get the benefits of modern healthcare technology. With the advent of personal computers (PC) at low cost, a PC based ECG equipment is also worth developing since many people already own a PC, thereby reducing the overall cost. With this view a PC based ECG equipment was designed and developed from the basics. An attempt was made to utilize maximum components and spares available in the local market. The main unit is based on a low cost but quality instrumentation amplifier IC with high common mode rejection ratio. Active filters were designed using common operational amplifier ICs. Right leg drive circuitry to reduce 50Hz noise of mains ac was kept as an option. Analog signal switching circuitry was used to obtain 12 Lead configurations, which were programme controlled, through graphical user interface. To achieve electrical isolation between patient and the mains ac, an analogue optical isolation circuit was designed and developed. Finally the analogue signal was converted to digital data and interfaced to a personal computer through its USB port using a microcontroller. The required power is obtained by USB port 5V supply. A medical grade isolated dc to dc converter was designed to power the patient side circuitry. Proper patient safety issues were followed in the design. Calibration was performed to make the equipment as accurate as possible. Outputs from several subjects were compared with that of reliable commercial equipment and were found to be satisfactory by cardiac experts. DOI: http://dx.doi.org/10.3329/bjmp.v6i1.19757 Bangladesh Journal of Medical Physics Vol.6 No.1 2013 39-54